A dor da perda de um filho: proposições práticas de conversações terapêuticas - Conti, Jetânia Maria Dawies de (2012)
This paper aims to seek the understanding of the experience of one set of parents facing the loss of a child, and understand feelings and reactions to a possible understanding of mourning. The methodological approach was supported by the phenomenology. It was used as an instrument of search the bibliography references. The phenomenological analysis of the subject reports the systematic understanding of the essential meanings in various categories: anger, guilt, grief and anxiety, loss of faith, grief, loneliness, depression, family crisis, physical sensations and behaviors in the face of loss. Also included are theories about the psychological counseling to the bereaved and some concepts such as death, grief, stages of grief, cycle of life and loss of a son. Search is indicative theorists to practice with bereaved parents, such as bereavement support group, family therapy, individual therapy and grief counseling, to assist in the reorganization of their lives after the death of a child